Emerging drugs for acute lung injury. (March 2015) - Impellizzeri, Daniela; Bruschetta, Giuseppe; Esposito, Emanuela; Cuzzocrea, Salvatore
<x xml:space="preserve">Abstract</x> Introduction: Acute respiratory distress syndromes (ARDS) are devastating disorders of overwhelming pulmonary inflammation and hypoxemia, resulting in high morbidity and mortality. Areas covered: The main pharmacological treatment strategies have focused on the attempted inhibition of excessive inflammation or the manipulation of the resulting physiological derangement causing respiratory failure. Additionally, such interventions may allow reduced occurence mechanical ventilation injury. Despite promising preclinical and small clinical studies, almost all therapies have been shown to be unsuccessful in large-scale randomized controlled trials. The evidence for pharmacological treatment for ARDS is reviewed. Potential future treatments are also presented. Expert opinion: We suggest for future clinical trials addressing prevention and early intervention to attenuate lung injury and progression to respiratory failure.